2016
DOI: 10.1093/infdis/jiw539
|View full text |Cite
|
Sign up to set email alerts
|

Schistosomal miRNAs isolated from Extracellular Vesicles in sera of infected patients; a new tool for diagnosis and follow-up of human schistosomiasis

Abstract: qRT-PCR of pathogen miRNAs isolated from extracellular vesicles in sera from infected individuals may provide a new tool for diagnosing schistosomiasis in patients with a low parasite burden. This assay could also be used for evaluating the outcome of therapy, as well as disease-control programs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
63
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 50 publications
(65 citation statements)
references
References 37 publications
1
63
0
1
Order By: Relevance
“…These results demonstrate an association between the schistosomal miRNAs and the EV fraction. These results are consistent with our previous data demonstrating schistosomal miRNAs in the fraction of EVs that were isolated from the sera of Schistosoma-infected patients [63]. In parallel, schistosomal-growth medium (used supernatant) was filtered through 0.1-lm membrane to deplete schistosomal EVs and placed on top of a trans-well above Th cells.…”
Section: Schistosomal-ev-enclosed Mirnas Penetrate Schistosomalexposesupporting
confidence: 92%
See 1 more Smart Citation
“…These results demonstrate an association between the schistosomal miRNAs and the EV fraction. These results are consistent with our previous data demonstrating schistosomal miRNAs in the fraction of EVs that were isolated from the sera of Schistosoma-infected patients [63]. In parallel, schistosomal-growth medium (used supernatant) was filtered through 0.1-lm membrane to deplete schistosomal EVs and placed on top of a trans-well above Th cells.…”
Section: Schistosomal-ev-enclosed Mirnas Penetrate Schistosomalexposesupporting
confidence: 92%
“…To further assess whether miRNAs were transferred by these EVs, the schistosomal EVs or the control pellets were added to the Jurkat cells. Forty-eight hours later, the RNA was extracted and subjected to qRT-PCR using the one-step real-time RT-PCR protocol that allows detection of very low amount of miRNAs [63]. The schistosomal miRNAs miR-125 and Bantam were detected in schistosomal-EV-exposed Jurkat cells but not in the control (Appendix Fig S4).…”
Section: Map3k7 (Tak1) Is a Target Of Schistosomal Mir-10mentioning
confidence: 99%
“…32 Another factor that needs to be considered when selecting EVs isolation protocols across different biofluids is the volume of starting material, as some biofluids may need to be concentrated prior to EVs isolation such as urine, an important source for patients diagnosed with renal pathologies, prostate and bladder cancers, 18 and other conditions including the parasitic infection schistosomiasis. 34 A recent study compared several filters and concluded that the best for recovering EVs from plasma, urine and EV-spiked PBS was a regenerated cellulose membrane with pores capable of retaining particles above 10 kDa. 35 Liang et al, have also demonstrated the feasibility of concentrating the EVs using a double-filtration microfluidic device capable of isolating, concentrating and quantifying urinary EVs, using 8 mL of the pre-filtered (0.22 μm filter) and 20 000g centrifuged urine-supernatant collected from bladder cancer patients and controls.…”
Section: Reviewmentioning
confidence: 99%
“…Circulating miRNAs have been studied and proposed as diagnostic biomarkers in many infectious diseases including malaria. Most studies on infectious diseases have detected human miRNAs such as those in tuberculosis [81], hepatitis B [82], schistosomiasis [83] while some studies investigated microbial miRNAs as biomarkers as well [57,[84][85][86]. Despite the fact that Plasmodium spp.…”
Section: Discussionmentioning
confidence: 99%
“…Hypergeometric distribution) was applied for enrichment analysis. The potential pathways were considered based on their p-value (p<0.05).Evaluation of potential EVs-derived miRNA as biomarkerMean of Delta Cq for each miRNA was used in this analysis following the previous study[57]. The Receiver Operating Characteristic (ROC) was calculated to propose the potential use of miRNAs as diagnostic tools.…”
mentioning
confidence: 99%